2017
DOI: 10.1111/jam.13351
|View full text |Cite
|
Sign up to set email alerts
|

Water activity and temperature effects on growth and mycotoxin production byAlternaria alternatastrains isolated from Malbec wine grapes

Abstract: Temperature and a conditions that allows growth and mycotoxin production are those normally found during wine grape ripeness in the field. Therefore, efforts should be made to prevent Alternaria presence and mycotoxin production in wine grapes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 35 publications
4
14
0
Order By: Relevance
“…In a previous work, we have found that temperature, a W , incubation time and strain type, were influencing factors in TA production by three A . alternata strains isolated from wine grapes in a synthetic nutrient media similar to grape composition (SN media) (Prendes et al., ). However, several works have demonstrated that fungal strains, producers of toxins in synthetic media, were not producers in natural substrates (Betina, ; Viñas et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous work, we have found that temperature, a W , incubation time and strain type, were influencing factors in TA production by three A . alternata strains isolated from wine grapes in a synthetic nutrient media similar to grape composition (SN media) (Prendes et al., ). However, several works have demonstrated that fungal strains, producers of toxins in synthetic media, were not producers in natural substrates (Betina, ; Viñas et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate these possibilities, this work analyzed for the first time TA production in wine grapes and the effect of temperature (15°C, 25°C, and 35°C) and incubation time (10, 17, and 24 days) using the three A . alternata strains that previously showed toxin production in a medium similar to grape composition (SN media) (Prendes et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations